Evaluation of the genetic diversity of domain II of Plasmodium vivax Apical Membrane Antigen 1 (PvAMA-1) and the ensuing strain-speciﬁc immune responses in patients from Sri Lanka - Dias, Sajani; Somarathna, Maheshika; Manamperi, Aresha; Escalante, Ananias A.; Gunasekera, Anusha M; Udagama, Preethi V. (Vaccine, 2011)
Antigenic polymorphism displayed by malaria parasites is a skewed schema to escape the host immune system. The prevailing genetic diversity at domain II of the Plasmodium vivax Apical Membrane Antigen-1 (Pvama-1DII) was characterized in 64 single clone P. vivax isolates from Sri Lanka, where unstable malaria prevails with low intensity. In Sri Lanka, the Pvama-1DII gene showed meager meiotic recombination with the enclosure of single nucleotide polymorphisms (SNPs). Eleven amino acid (a.a.) variant positions defined 21 a.a. haplotypes with 9 unique to the island, where the predominant haplotype, H1, was identical to the reference Salvador I strain. A further 376 globally dispersed isolates defined 38 a.a. haplotypes (H22–H59), with 4 and 26 haplotypes exclusive to India and Thailand, respectively. The phylogenetic tree revealed no clustering, where most isolates had a very recent common origin. The polymorphism detected in PvAMA-1DII B and T cell epitopes evidenced an immune evasion mechanism exploited by the parasite. Majority of Sri Lankan patients developed antibody responses to both conformational and linear B cell epitopes. The ensuing strain-specific immunity due to extensive antigenic polymorphism was evaluated by aligning a.a. sequences of PvAMA-1DII with the homologous total (IgM + IgG) antibody responses assayed by in-house established indirect ELISAs against 7 PvAMA-1DII overlapping synthetic peptides, P01–P07. While the antibody responses to P01–P03, P06, P07 harbouring P. vivax clinical isolates with polymorphic a.a. haplotype to Sal I was clearly strain-transcending (cross-reactive), individuals with isolates identical to the Sal I strain observed varying antibody prevalence against the seven PvAMA-1DII Sal-I synthetic peptides, with the highest prevalence detected against P04. Synthetic peptide P04, spanning a.a. positions 302–324 of the PvAMA-1DII of the Sal I strain that included the epitope recognized by the invasion inhibitory 4G2 monoclonal antibody of PfAMA-1, was highly conserved in all 440 local and global P. vivax isolates examined. A functional role for this region is reinforced by the highly immunogenic nature of P04, and could point towards a presumably “protective” anti-P04 antibody response that elicited an isotype switch from IgM to IgG, with increasing exposure to malaria exclusively in endemic residents. Thus the conserved and seemingly “protective” nature of the domain II loop of PvAMA-1 makes it a putative contender to be included in a cocktail vaccine against P. vivax asexual erythrocytic stages in Sri Lanka.
Highlights ► Meager meiotic recombination and single nucleotide polymorphisms affected genetic diversity at Pvama-1DII in Sri Lanka. ► Eleven a.a. variant positions defined 21 a.a. haplotypes with 9 unique to the island. ► Majority of Sri Lankan patients developed anti-AMA-1 antibodies to both conformational and linear B cell epitopes. ► The PvAMA-1DII loop was highly conserved in all local and global isolates. ► Highly immunogenic P04 peptide with protective antibody response is a strong contender for a vaccine construct.
Keywords: Sri Lanka; Plasmodium vivax; genetic diversity; Apical Membrane Antigen 1; Domain II; Strain specific immune response